(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of our study is to know the association between gingival recession and its biotype among the South Indian population.Materials And Methods: The study was conducted between September 2020 and March 2021, 86000 patient records were analysed, with 106 patients meeting the inclusion and exclusion requirements being included in the report. Gingival recession and the history and type of smoking habits were recorded. SPSS software was used to perform statistical analysis on the results.Results: After analysing the results around 56.6% of the patients had thin gingival biotype when it was related with clinical attachment loss. The prevalence of thick and thin gingival biotypes was found to be 43.39 percent and 56.6 percent, respectively, with no significant relationship between age, gender and association of gender and gingival biotype.Conclusion: This research could be useful in predicting the case's prognosis. Patients with a thin biotype have a higher incidence of gingival recession, so treatment modalities aimed at increasing gingiva thickness can improve the treatment outcome of recession coverage procedures.